Więcej niż obraz – metody dokumentacji zabytków architektury z wykorzystaniem HBIM. Przykład siedziby Instytutu Historycznego Uniwersytetu Wrocławskiego - Urszula Kwast-Kotlarek; Agnieszka Seidel-Grzesińska (Quart)
The paper addresses the question of whether it is possible to secure information about a listed architectural object when it is comprehensively renovated with regard to specific functional uses. The subject of the consideration is the seat of the Historical Institute of the University of Wrocław – a building complex with a multifaceted history that has undergone thorough renovation and conservation work in recent years. The origins of the complex date back to the turn of the 13th to 14th century, and it has experienced changes in almost every subsequent century. At the end of the 19th century, the complex received its current form as a four-winged structure with a courtyard in the middle and a facade facing Szewska Street. This renovation, which adapted the buildings to the needs of a police headquarters, was intended to erase the traces of the complex’s older, historical functions. However, the current renovation works have brought to light numerous valuable relics from each phase of its use. The article discusses methods for the visual representation of an architectural object and its elements, which facilitate the preservation of information obtained during renovation works for potential use in the HBIM environment.